Predictive Feedback Linearization Tracking Control for WMR Systems with Control Delay. Issue 1 (13th June 2021) - Huang, Yu-Mei; Lei, Jing
Abstract: This article addresses the control design problem for nonlinear wheeled mobile robot (WMR) tracking with a control delay. The tracking model is built by WMR dynamical equation. The state-space representations of the controlled WMR motion system and the dynamical target system are obtained by transformations. Then, the tracking error system with control delay is achieved and a feedback linearization delayed control is presented. The physical implement problem of the predictive control is solved by constructing a high-gain predictor, based on which the predicted states in feedback linearization controllers are estimated by the predictive states. The simulation results demonstrate that the physical implement problem are solved well by using high-gain predictor. The target path are successfully tracked by the designed feedback linearization controllers of state feedback and output feedback.